(toward) a phenomenology of acting - Zarrilli, Phillip B. (Routledge, 2020)
"In (toward) a phenomenology of acting, Phillip Zarrilli considers acting as a 'question' to be explored in the studio, and then reflected upon. This book is a vital response to Jerzy Grotowski's essential question: "How does the actor 'touch that which is untouchable?'" Phenomenology invites us to listen to "the things themselves", to be attentive to how we sensorially, kinaesthetically, and affectively engage with acting as a phenomenon and process. Using detailed first-person accounts of acting across a variety of dramaturgies and performances from Beckett to newly co-created performances to realism, it provides an account of how we 'do' or practice phenomenology when training, performing, directing, or teaching. Zarrilli brings a wealth of international and intercultural experience as a director, performer, and teacher to this major new contribution both to the practices of acting, and how we can reflect in depth on those practices. An advanced study for actors, directors, and teachers of acting that is ideal for both the training/rehearsal studio and research, (toward) a phenomenology of acting is an exciting move forward in the philosophical understanding of acting as an embodied practice"--